Communication for consultants - Owens, Rita R. (New York, New York (222 East 46th Street, New York, NY 10017) : Business Expert Press, 2016)
From the moment of their first client engagement, consultants in all fields face communication opportunities and challenges. No matter what their focus may be--professional services, accounting, technology, operations, human resources, manufacturing, or marketing--consultants drive change. That change, from its initial definition through its development and deployment, must be precisely communicated to a variety of audiences and through a variety of mediums. Most business communication books do a good job leading professional writers and presenters through the basics of audience, organization, formatting, and mechanics. But, only few focus on a specific business role, such as that of a consultant, and give guidance for communicating during all stages of a project. From the pre-engagement process, to the actual engagement, to the post-engagement follow-up, consultants are challenged by the variety of audiences whose roles continually shift throughout a project. This book guides a current or would-be consultant through the various phases of a typical engagement and gives practical advice and direction on written and oral communication throughout a project. Current and future consultants in all fields will gain specific knowledge about writing and presenting to a variety of audiences including clients, team members, managers, and executives.
1. Key considerations for consultants -- 2. Pre-engagement communication -- 3. Engagement communication -- 4. Post-engagement communication -- Appendix A -- Appendix B -- Notes -- References -- Index.
Includes bibliographical references (page [115]) and index.
Title from PDF title page (viewed on June 12, 2016).
Electronic reproduction. Ann Arbor, MI : ProQuest, 2016. Available via World Wide Web. Access may be limited to ProQuest affiliated libraries.
Keywords: Business communication; Business consultants; business communication; business correspondence; business etiquette; business writing; consulting; e-mails; engagements; meetings; presentations; proposals; reports; Electronic books